The mechanism of intestinal flora dysregulation mediated by intestinal bacterial biofilm to induce constipation. Issue 1 (1st January 2021) - Fu, Ruibiao; Li, Zhongpeng; Zhou, Rui; Li, Chaoyang; Shao, Shuai; Li, Jin
ABSTRACT: To explore mechanism of intestinal flora dysregulation promoting constipation, 60 specific pathogen-free (SPF) mice were used as research objects and were treated with constipation population fecal fluid gavage and distilled water gavage. Then, relationship between intestinal dysregulation and constipation in mice with biofilm-mediated intestinal flora was investigated in vitro. The results showed that recombinant serotonin transporter (SERT) messenger ribonucleic acid (mRNA) level of the constipation population fecal fluid gavage group and the relative expression level of SERT mRNA were 1.61 ± 0.08 and 1.49 ± 0.06, which were higher markedly than those of distilled water group ( P  < 0.05). The level of 5-hydroxytryptamine (5-HT) in colonic tissue of the constipation population fecal fluid gavage group was 145.36 ± 14.12 ng/mL, and the expression level of 5-HT on the surface of epithelial cells of biofilm-positive colonic tissue was 20.11 ± 2.03, which were significantly lower than those of the distilled water group, with statistical significance ( P  < 0.05). Besides, the microbial sequencing of fecal flora indicated that The Akk and bacteroidetes ofconstipation population fecal fluid gavage group were higher hugely than those of distilled water group ( P  < 0.05).In conclusion,  after the occurrence of constipation, the diversity of intestinal microflora decreased, and the probiotics reduced. Iintestinal microflora dysregulation would lead to increase of SERT expression level in defecation function and intestinal motility in mice, and the decrease of 5-HT,  thereby changing the intestinal movement resulting in mucosal protective barrier damage, thereby causing changes in intestinal movement and the destruction of the intestinal mucosal protective barrier, which eventually resulted in constipation. The occurrence of constipation could be improved by regulating balance of intestinal flora, increasing the diversity of flora, and reducing the genus of opportunistic pathogens.